2018
DOI: 10.3390/molecules23102584
|View full text |Cite
|
Sign up to set email alerts
|

High Potency of Melaleuca alternifolia Essential Oil against Multi-Drug Resistant Gram-Negative Bacteria and Methicillin-Resistant Staphylococcus aureus

Abstract: Purpose: Herein, an extended investigation of Tea tree oil (TTO) against a number of multi-drug resistant (MDR) microorganisms in liquid and vapor phases is reported. Methods: The activity of TTO was tested against methicillin-sensitive Staphylococcus aureus (MSSA), Escherichia coli, and clinical strains of methicillin-resistant S. aureus (MRSA), extended-spectrum beta lactamases producer carbapenem-sensitive Klebsiella pneumoniae (ESBL-CS-Kp), carbapenem-resistant K. pneumoniae (CR-Kp), Acinetobacter baumanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 52 publications
2
49
0
1
Order By: Relevance
“…Besides the impact of the DFM, phytogenic feed additives may have an effect on the prevalence of ESBL-PE [47,48]. A reduction of ESBL-PE prevalence was observed both qualitatively and quantitatively in the presence of the phytogenic products in cecal contents.…”
Section: Discussionmentioning
confidence: 96%
“…Besides the impact of the DFM, phytogenic feed additives may have an effect on the prevalence of ESBL-PE [47,48]. A reduction of ESBL-PE prevalence was observed both qualitatively and quantitatively in the presence of the phytogenic products in cecal contents.…”
Section: Discussionmentioning
confidence: 96%
“…Scientists have also found that the solubility of EO in water allowed them to decipher how EOs penetrated the cell wall of microbes; in other words EOs, being soluble in the cell membrane phospholipid bilayer, diffuse through the membrane [74]. A study done using the EO of Melaleuca alternifolia (tea tree) against MDR gram-negative bacteria (e.g., Escherichia coli and carbapenem-resistant K. pneumoniae) and methicillinresistant S. aureus (MRSA) showed that there is a bactericidal effect of tea tree EO on these microorganisms [75]. This indicated that the EO can be used to kill resistant bacteria [74].…”
Section: Use Of Essential Oils Against Multidrug-resistant Bacteriamentioning
confidence: 99%
“…Synergistic interaction is when the effect of the combined chemicals is greater than the effect of a chemical alone; additive interaction is when the sum of two chemicals is equal to the sum of chemical effect alone, while antagonism is when the whole effect of the two chemicals is less than the sum of effect of a single chemical alone [86]. In a study performed using the tea tree EO against the MDR bacteria, when a combination of tea tree EO with antibiotic (e.g., oxacillin) was tested on the bacteria, in particular the MRSA, a high synergistic index in the sub-inhibitory concentration was recorded [75]. This indicates that the EO can be used to overcome bacterial resistance to antibiotic.…”
Section: Mechanisms Of Actions With Antibioticmentioning
confidence: 99%
“…When the TTO contains 30% to 40% of terpinen-4-ol, identified as the most effective antimicrobial component, it is referred to as terpinen-4-ol chemotype [21,22]. TTO possesses antimicrobial properties also against multi-drug resistant Gram-negative bacteria and methicillin-resistant Staphylococcus aureus [23,24]. Rosmarinus officinalis Linnaeus (1753, Lamiaceae), is a plant native to the Mediterranean area, but cultivated worldwide, known for its nutritional value and pharmacological properties (e.g., anti-inflammatory, antiparasitic and antimicrobial) [25,26].…”
Section: Introductionmentioning
confidence: 99%